PENGARUH KEPUASAN KERJA TERHADAP KINERJA KARYAWAN DAN KEPUASAN PELANGGAN PADA RUMAH SAKIT SWASTA DI KOTA DENPASAR - Indrawati, Ayu Desi (Matrik : Jurnal Manajemen, Strategi Bisnis, dan Kewirausahaan; Volume 7 Nomor 2 Tahun 2013, 2013)
This  study aimed  to  determine  the  effect  of  job   satisfaction  on  employee  performance,  employee  performance to customer satisfaction, and job satisfaction on customer satisfaction through employee performance. This study took place in hospitals-private hospital in Denpasar, sing hospital employees and patients as research respondents. Proof of this hypothesis using path analysis techniques.The results obtained  in  this  study  that  are:  1)  job  satisfaction  have  significant  positive  impact on  employee performance, 2) the performance of the employee significant positive effect on customer satisfaction, and 3) positively influence job satisfaction directly and indirectly through the employee’s performance to customer satisfaction.
Keywords: job satisfaction, employee performance, customer satisfaction